Conflict Management Strategies as Predictor of Peace Culture among Undergraduate Students in Ogun State, Nigeria - Ogunsanwo, Mojisola A. (NIU Journal of Social Sciences; Vol 7 No 1 (2021): KIU Journal of Social Sciences, Vol. 7 No. 1, March 2021, 2021)
This study investigated the impact of conflict management strategies in maintaining peace culture in academia especially among the undergraduates. The study adopted a descriptive survey research design of an ex post facto type. Two research hypotheses were formulated and tested at 0.05 level of significance. Data were collected using a self-developed instrument and one already validated instrument. The questionnaire was administered on a sample of 1800 participants that were randomly selected from 6 universities in South West Nigeria. Data were analysed using descriptive analysis, regression and t-test Statistical Analysis. The findings of this study indicated significant prediction of the use of conflict management strategy on peace culture among undergraduates (F (1,1798) = 18.709; P < .000). The study also indicated a significant difference in the undergraduate perception of university peace culture (MD = 8.38; t = 5.205; P <.05). It is therefore recommended that the school management should ensure that non-violent means is employed as an intervention technique for conflict resolution in schools. This will encourage peaceful co-existence and teamwork between students, staffs and other members of the school community. Keywords: conflict management, strategies, peace culture, undergraduates